2x-1=z+8-2z

Simple and best practice solution for 2x-1=z+8-2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-1=z+8-2z equation:


Simplifying
2x + -1 = z + 8 + -2z

Reorder the terms:
-1 + 2x = z + 8 + -2z

Reorder the terms:
-1 + 2x = 8 + z + -2z

Combine like terms: z + -2z = -1z
-1 + 2x = 8 + -1z

Solving
-1 + 2x = 8 + -1z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 2x = 8 + 1 + -1z

Combine like terms: -1 + 1 = 0
0 + 2x = 8 + 1 + -1z
2x = 8 + 1 + -1z

Combine like terms: 8 + 1 = 9
2x = 9 + -1z

Divide each side by '2'.
x = 4.5 + -0.5z

Simplifying
x = 4.5 + -0.5z

See similar equations:

| 3x-x=7-x | | -2/5r=-20 | | 8-8x+3=11 | | 6=f-3 | | 6(3x)= | | 6=f | | 0.3x+2=0.8x+4 | | -4=-6a+2a | | -(1+35)-6-35=36 | | 2(4c-1)-2=6c+6 | | -8m+5m=-9 | | -3v=-4x | | 10d-6=1d-15 | | 4/3h=12 | | 3(x+5)=5(x-2) | | 6=b+8+b | | 6v^2=24 | | y=-(2/3)x+3 | | 0/1110 | | -3(1+5x)-8=94 | | -77=-5(7m-4)-2(m-7) | | 8x-9=1+x | | r-(-36)=5 | | 6a(-5+3)-14=6a-12+25 | | -3(1+5x)-7=94 | | 7.8k-2.14=-42.7 | | Ax-7=box+4 | | m-1/6-4m+5/6=0 | | -5(y-7)=3y-29 | | -x^2+21x-104=0 | | 2.3w-(7)+8.1-3w=0 | | 0.2x+3.4+0.8x=4 |

Equations solver categories